2015
DOI: 10.1016/j.ijlp.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Unloading the hired gun: Inoculation effects in expert witness testimony

Abstract: The current projects investigated the efficacy of inoculation as a trial strategy designed to counter mock jurors' perceptions that an expert is a hired gun. Additionally, the projects also examined whether the manner in which experts responded to these questions had a significant effect on their ratings as a hired gun and overall credibility. The project contained two independent studies with parallel manipulations. Study 1 examined the previously mentioned effects in a civil trial while study 2 examined them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…It is important to note, however, that we observed no backfire effect from the prosecution's inoculation effort, suggesting that prosecution attorneys may suffer no harm from seeking to develop a more effective inoculation statement. Our inoculation testimony acknowledged the risk of error but explained why that risk was not present here; one alternative approach would be to seek to undercut the credibility of the anticipated rebuttal expert, perhaps by characterizing that expert as a ‘hired gun’ (Ziemke & Brodsky, 2015) or with evidence of that expert's own prior mistakes. Given the potential impact of rebuttal testimony on juror perceptions of forensic evidence, the parties have a strong interest in developing effective counter‐measures.…”
Section: Discussionmentioning
confidence: 93%
“…It is important to note, however, that we observed no backfire effect from the prosecution's inoculation effort, suggesting that prosecution attorneys may suffer no harm from seeking to develop a more effective inoculation statement. Our inoculation testimony acknowledged the risk of error but explained why that risk was not present here; one alternative approach would be to seek to undercut the credibility of the anticipated rebuttal expert, perhaps by characterizing that expert as a ‘hired gun’ (Ziemke & Brodsky, 2015) or with evidence of that expert's own prior mistakes. Given the potential impact of rebuttal testimony on juror perceptions of forensic evidence, the parties have a strong interest in developing effective counter‐measures.…”
Section: Discussionmentioning
confidence: 93%
“…It cannot be ruled out that legal decision makers already more critically evaluate information from psychological experts who also treat the litigating victim than information from independent experts. The former may be seen as hired guns —experts who simply take the position of their client in return for payment (Ziemke & Brodsky, 2015 ). Several studies suggest that the opinion of such experts is often considered with suspicion by legal decision makers (see Edens, Smith, Magyar, Mullen, Pitta, & Petrila, 2012 ; Mossman, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lieberman et al [26] found DNA evidence strongly influenced guilty decisions, even after a cross-examination. Ziemke and Brodsky [27] examined an "inoculation tactic," whether having an expert acknowledge during direct examination he was being paid and often testified for defendants would neutralize a prosecution effort to portray the expert as a "hired gun;" they found no effects of doing so. Thompson and Scurich [28] found mock jurors rated a forensic odontologist as less credible and were less likely to convict when the examiner admitted on cross examination that the bitemark examination rested on his subjective judgment, and that he was exposed to potentially biasing task-irrelevant contextual information, relative to when these issues were not raised.…”
mentioning
confidence: 99%